2016
DOI: 10.1056/nejmoa1414838
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the sFlt-1:PlGF Ratio in Women with Suspected Preeclampsia

Abstract: An sFlt-1:PlGF ratio of 38 or lower can be used to predict the short-term absence of preeclampsia in women in whom the syndrome is suspected clinically. (Funded by Roche Diagnostics.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
890
3
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,276 publications
(1,043 citation statements)
references
References 39 publications
48
890
3
23
Order By: Relevance
“…l the PROGNOSIS study, reported in a company submission to NICE provided by Roche Diagnostics, 61 an unpublished academic manuscript 73 that was subsequently published by Roche Diagnostics (Zeisler et al 51 ), a meeting abstract (Zeisler et al…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…l the PROGNOSIS study, reported in a company submission to NICE provided by Roche Diagnostics, 61 an unpublished academic manuscript 73 that was subsequently published by Roche Diagnostics (Zeisler et al 51 ), a meeting abstract (Zeisler et al…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Instead, ultrasonography and maternal serum protein markers have been pursued to noninvasively monitor placental function during pregnancy (3,4). It has been shown that the placenta is the major source of circulating cell-free fetal nucleic acids in maternal plasma (5)(6)(7).…”
mentioning
confidence: 99%
“…Les concentrations de sENG et le ratio sFLT1/PlGF se sont également avérés être augmentés en cas de PE. Les valeurs prédictives positives de ces mesures, seules, avant 20 semaines d'aménorrhée, restent cependant faibles alors que les valeurs prédictives négatives sont excellentes, ce qui permet de discriminer, dans une population à risque, les femmes qui ne développeront pas de PE précoce [40]. Les outils actuels (paramètres cliniques, histoire médicale de la patiente, facteurs angiogéniques) sont utiles pour différencier les femmes présentant des symptômes de PE mais avec un profil angiogénique normal et un risque faible de complications liés à la PE sévère.…”
Section: Les Cellules Endothélialesunclassified